Gerakan Jender dan Implikasinya terhadap Pendidikan Anak - Siti Aisyah Abbas (Jurnal Adabiyah: Humanities and Islamic Studies, 2010)
In Islamic perspective children must be guided by parents to reach their good progress. Thus, the of parents cannot be ignored in the framework of educating, guiding and directing the potency of children. In this case, parents are required to know more about character of children, emotion and mentality. One of parents' duty in their home is introducing gender concept to children. Gender discourse about the right and responsibility of children in any aspect should be socialized .